Novel bifunctional mesoporous catalysts based on preyssler heteropolyacids for green pyrrole derivative synthesis - Portilla Zúñiga, Omar Miguel (2018)
In this paper, we report the synthesis of Preyssler heteropolyacids supported on mesoporous alumina in order to obtain materials with acid–base properties. A series of pyrrole derivatives were synthesized using a suitable procedure under solvent-free conditions. Using the alumina-supported material, more complex pyrrole derivatives can be obtained through a tandem one-pot process that involves the formation of 2-amino-3-cyano 4-H-chromenes by a multicomponent reaction and their subsequent conversion to pyrrole using a Paal–Knorr reaction.